2000
DOI: 10.2214/ajr.175.1.1750053
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Stereotactic 11-Gauge Directional Vacuum-Assisted Breast Biopsy

Abstract: Stereotactic 11-gauge directional vacuum-assisted breast biopsy obviated a surgical procedure in 76% of lesions, yielding a 20% decrease in cost of diagnosis compared with surgical biopsy. Although savings per case are modest, 11-gauge directional vacuum-assisted biopsy expands the spectrum of lesions amenable to stereotactic biopsy, increasing cost savings in the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
2
15

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 29 publications
2
34
2
15
Order By: Relevance
“…Acceptable underes- timation rates and false-negative rates of this procedure have been reported by experienced radiologists (12). VASB decreases the cost of diagnostic procedures compared with surgical excisional biopsy (13 There are some limitations to this study. First, the follow-up period for some lesions was too short; although lesions with less than one year of follow-up were in the minority.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Acceptable underes- timation rates and false-negative rates of this procedure have been reported by experienced radiologists (12). VASB decreases the cost of diagnostic procedures compared with surgical excisional biopsy (13 There are some limitations to this study. First, the follow-up period for some lesions was too short; although lesions with less than one year of follow-up were in the minority.…”
Section: Discussionmentioning
confidence: 88%
“…The false-negative rate of VASB procedure can be as low as 0.6% when performed by experienced radiologists (12). This technique also has some cost advantages compared to needle-localized surgical biopsy (NLSB) (13).…”
mentioning
confidence: 99%
“…33 35 The diagnostic characterization of NPBL has progressed markedly over the past years with the advent of stereoguided needle biopsy techniques that eliminate unnecessary surgical resection of benign lesions while carrying a low rate of missed cancers among the lesions not excised. 5,[36][37][38][39][40] Surgical management of these lesions should evolve with the primary objectives of improving localization and limiting tissue trauma. In an earlier study we confirmed that the ABBI method was a safe and accurate biopsy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Während bei etwa 40% der histologischen Diagnosen einer atypischen duktalen Hyperplasie bei der Hochgeschwindigkeitsstanzbiopsie intraoperativ ein DCIS (duktales In-situ-Karzinom) gefunden wird, liegt dieser Anteil bei den vakuumunterstützten Verfahren bei etwa 15% [25][26][27][32][33][34][35]. Immer dann, wenn im Biopsat die Diagnose einer atypischen duktalen Hyperplasie gestellt wird, sollte noch eine offene Probeexzision erfolgen [3].…”
Section: Ergebnisse Und Wertung Der Minimal-invasiven Biopsietechnikenunclassified
“…Als nachteilig ist der relativ hohe Preis der Verbrauchsmaterialien bei den vakuumunterstützten Verfahren im Vergleich mit der Hochgeschwindigkeitsstanzbiopsie zu bewerten. Da bei geeigneter Indikation, wie zum Beispiel bei suspektem Mikrokalk in der Mammographie, mit diesen Verfahren auch bei Läsionen der BI-RADS-Kategorie 4 häufig die offene PE vermieden werden kann, sind diese auch unter Kostengesichtspunkten vertretbar [35], zumal vorhandene OP-Kapazitäten dann für Patientinnen mit minimalinvasiv nachgewiesenen Mammakarzinomen zur Verfü-gung stehen und nicht durch offene diagnostische Operationen mit dann endgültig benigner Histologie blockiert werden.…”
Section: Ergebnisse Und Wertung Der Minimal-invasiven Biopsietechnikenunclassified